Students’ Perception of Using Artificial Intelligence (AI) Chat-GPT as a Writing Assistance - Desi Fitriani; Mohammad Muhassin; Nur Syamsiah (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This study aims to determine students' perceptions of the use of ChatGPT as a writing tool, focusing on the indicators of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) from the theoretical framework of the Technology Acceptance Model (TAM). This study uses a non-experimental quantitative survey design. Data were collected from 30 fifth semester English Education students at UIN Raden Intan Lampung, selected using purposive sampling. The instrument used was a 5 point Likert scale questionnaire consisting of 20 statements, with analysis using descriptive statistics. The research findings show that students have a positive perception of ChatGPT, with an overall average score (M = 4.2621) in the high category. The PU results (M = 4.2867) were slightly higher than the PEOU (M = 4.2375). The high PU average indicates that students feel the greatest benefits of ChatGPT in completing tasks more quickly (M = 4.40), helping to generate initial ideas (M = 4.33), and organizing writing (M = 4.30). Similarly, the high PEOU results indicate that students find ChatGPT easy to use for their writing needs (M = 4.37) and easy to learn. These findings imply that ChatGPT is considered useful as a helpful and easy to operate tool in writing activities.